2002
DOI: 10.1177/154193120204601204
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Individual Differences in Decision Making Styles: Analytical vs. Intuitive

Abstract: Decision strategies are often characterized as being intuition-based or analytically-based. The use of these strategies is proposed to be associated with individual differences in propensity toward using different decision making styles. A reliable self-report measure, the Decision Making Styles Inventory (DMI), consisting of 15 items on each of three scales was constructed. The items were found to differentiate among an "analytical", an "intuitive", and a "regret-based" emotional decision making style. The an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
6

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 5 publications
1
27
0
6
Order By: Relevance
“…Downloaded by [Cambridge University Library] In addition, Fabbri, Antonietti, Grorgetti, Tonetti, and Natale (2007) associated morning types with left-brain thinking, which follows analytic, sequential, and conservative models of reasoning; evening types, by contrast, were associated with right-brain thinking, which processes information in intuitive, imaginative, feeling-guided ways. Future-time perspectives and left-brain thinking are negatively related to risk taking (Nygren & White, 2002;Zimbardo, Keough, & Boyd, 1997). All of these findings support the premise that morning types are less likely to engage in risky behaviors than other types are.…”
Section: Morning Types Evening Types and Risk Takingsupporting
confidence: 64%
“…Downloaded by [Cambridge University Library] In addition, Fabbri, Antonietti, Grorgetti, Tonetti, and Natale (2007) associated morning types with left-brain thinking, which follows analytic, sequential, and conservative models of reasoning; evening types, by contrast, were associated with right-brain thinking, which processes information in intuitive, imaginative, feeling-guided ways. Future-time perspectives and left-brain thinking are negatively related to risk taking (Nygren & White, 2002;Zimbardo, Keough, & Boyd, 1997). All of these findings support the premise that morning types are less likely to engage in risky behaviors than other types are.…”
Section: Morning Types Evening Types and Risk Takingsupporting
confidence: 64%
“…Decision making styles The Decision Making Style Inventory (Nygren, 2000;Nygren & White, 2002), composed of three 15-item scales, was used to measure decision making styles. Analytical decision making is the propensity to engage in effortful deliberation in choice situations (e.g., "In making decisions I try to evaluate the importance of each piece of information in the decision process.").…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies of the relationship between the maximization behavior and measures of well-being included criterion variables measuring regret, decision making styles, subjective happiness and optimism scales (Diab et al, 2008;Nenkov et al, 2008;Parker, Bruin, & Fischhoff, 2007;Schwartz et al, 2002). In an attempt to replicate this previous research for our new scales, we included the Decision Making Style Inventory (Nygren, 2000; Nygren & White, 2002), the Life Orientation Test as a measure of optimism (Scheier, Carver, & Bridges, 1994), the General Self-efficacy Scale (Sherer et al, 1982), the Unconditional Self-regard Scale (Betz, Wohlgemuth, Serling, Harshbarger, & Klein, 1995), and the Subjective Happiness Scale (Lyubomirsky & Lepper, 1999). Based on the findings of Parker et al (2007) and Rim et al (2011), we postulated that maximizers (i.e., participants with higher scores on decision difficulty and alternative search) would score highly on maladaptive decision making styles, whereas satificers (i.e., participants scoring highly on our new satisficing scale) would score more highly on positive adaptive decision making styles and in particular, the analytical decision making style.…”
Section: Study 2: Correlation Study With the New Scalementioning
confidence: 99%
“…Results from two studies (Nygren, 2000;Nygren & White, 2002) suggested that the tendency toward either an analytic or intuitive decision style can affect performance on complex tasks performed by pilots during simulation training. A reliance on an analytical decision style led to poorer performance than an intuitive approach when there were multiple sub-tasks, each with its own performance criteria.…”
Section: Decision Making Style Inventorymentioning
confidence: 99%